(untitled) (International Journal of Engineering and Computer Science, 2017)
The cloud is redefining the IT architectures of various business domains. Organizations have clearly recognized the unlimited benefits of cloud like dynamic payloads on the technical side and elastic financial models on the commercial side which guarantees in greater than before efficiency. The benefits of cloud computing can be maximized fully by applying novel technologies in security and risk management processes. The risk factors in terms of security is much more in public cloud computing compared to traditional computing which are bases on datacenter . In a highly shared ad hoc cloud environment which is in the control of instance-to-instance network connectivity security of the applications and sensitive data is a big challenge faced by the cloud providers. As the entire stack of applications, platform, infrastructure of the cloud is designed and managed by service providers the cloud users are uncertain about the security. This paper studies the generic security challenges in an ad hoc cloud environment .the security challenges and mitigations are discussed in section I. A survey was conducted with users of cloud from domains like health care, education and retail business. Analysis of survey data and the results are also discussed in section